Assessing the affective load in the narratives of women suffering from fibromyalgia: the clinicians' appraisal. (10th December 2014) - Cedraschi, Christine; Girard, Elodie; Piguet, Valérie; Desmeules, Jules; Allaz, Anne‐Françoise
Abstract: Objective: Fibromyalgia is characterized by chronic widespread pain and various associated symptoms, including psychological distress. This study presents a secondary analysis of the interviews of patients with fibromyalgia to appraise the affective load of the patient narratives as assessed by independent clinicians. Setting and participants: Three clinicians, an internist, a psychiatrist and a psychologist, who were experienced in chronic pain reviewed the interview transcripts of 56 women eliciting their views regarding fibromyalgia onset. A Clinical Global Impression (CGI) scale was used (0 = no affective load to 5 = maximum affective load) to provide a subjective appraisal of the intensity of the affective impact, as suggested in the transcripts and from the clinician perspectives. Results: The mean affective load was 3.6 (SD = ±1), indicating the perception of a high affective load in the clinicians. Values indicating a high or very high affective load (≥4 points on the CGI scale) were more frequent than those in the lower range [23 narratives (41%) vs. 3 (5%)]. The inter‐rater agreement of the affective load of the narratives was high ( K  > 0.85). These results of the clinician perspectives parallel those of the patient narratives, emphasizing disruptive circumstances, psychological distress and hopelessness surrounding symptom onset. Conclusion: The affective load in the narratives of these patients with fibromyalgia was high and had a negative undertone when considered from the clinicians' perspective. This study highlights the importance of considering the affective resonance in the context of therapeutic relationships that are often emotionally laden and highly challenging for the clinician.